2018
DOI: 10.1177/0192513x18800766
|View full text |Cite
|
Sign up to set email alerts
|

Racial Socialization Practices Among White American Parents: Relations to Racial Attitudes, Racial Identity, and School Diversity

Abstract: This study examines racial socialization practices among White American parents (N = 154) of children aged 8 to 12 years, using both quantitative and qualitative measures, as well as the relations of racial attitudes, racial identity, and racial diversity of the schools that children attend to socialization practices. Responses on the qualitative socialization measure indicate that White parents are generally unlikely to discuss race or racism with their children in a direct, explicit fashion, even when the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(145 citation statements)
references
References 39 publications
(119 reference statements)
6
127
2
Order By: Relevance
“…Studies that ask White parents to report on racial discussions with their children suggest that a sizable minority of parents engage in these discussions already. Recent estimates indicate that approximately 30% of White parents in the U.S. are able to recall specific examples of race discussions with their children (Vittrup, 2018;Underhill, 2017;Zucker & Patterson, 2018). For instance, we found that 37% of White parents had discussed contemporary race-related events (e.g., the deaths of Michael Brown and Trayvon Martin, or the Charleston shooting) with their child (Perry et al, 2019).…”
Section: Advantages Of Explicit Racial Socialization Conversationsmentioning
confidence: 71%
“…Studies that ask White parents to report on racial discussions with their children suggest that a sizable minority of parents engage in these discussions already. Recent estimates indicate that approximately 30% of White parents in the U.S. are able to recall specific examples of race discussions with their children (Vittrup, 2018;Underhill, 2017;Zucker & Patterson, 2018). For instance, we found that 37% of White parents had discussed contemporary race-related events (e.g., the deaths of Michael Brown and Trayvon Martin, or the Charleston shooting) with their child (Perry et al, 2019).…”
Section: Advantages Of Explicit Racial Socialization Conversationsmentioning
confidence: 71%
“…Our systematic review of the empirical literature in the 2010 decade confirmed D. L. Hughes, Del Toro, and Rarick's () observation that there is limited empirically based knowledge about the predictors or correlates of egalitarianism. Of the 15 studies we identified, nine focused on exploring and identifying factors that informed parents' use of this ethnic–racial socialization strategy (e.g., Cooper, Smalls‐Glover, Neblett, & Banks, ; Hagerman, ; Zucker & Patterson, ) and six examined the associations between messages of egalitarianism and youth outcomes (see Table ). As noted in Table , a majority found that egalitarianism promoted positive adjustment among youth (e.g., stronger integrated identity and higher self‐esteem [Villegas‐Gold & Tran, ]; higher academic expectations [Trask‐Tate, Cunningham, & Francois, ]); one study reported mixed findings (French, Coleman, & DiLorenzo, ), and one study reported null findings (White‐Johnson, ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…In addition to our primary interest in developmental processes, we highlight the role of social‐justice issues in the realm of political thought and participation. Collectively, our past research has focused on the formation, function, and revision of youths’ attitudes about social groups, including those based on gender or sex (e.g., Bigler & Liben, , ; Bigler, Hayes, & Liben, ; Hayes, Bigler, & Weisgram, ; Hayes, Pahlke, & Bigler, ; Leaper & Brown, ; Pahlke, Bigler, & Green, ; Pahlke, Bigler, & Martin, ; Pahlke, Hyde, & Allison, ; Patterson, 2012; Patterson & Pahlke, ), race or ethnicity (Bigler & Liben, ; Brown, ; Brown, Mistry, & Bigler, ; Hughes, Bigler, & Levy, ; Pahlke, Bigler, & Suizzo, ; Zucker & Patterson, ), and immigrant status (Brown, ; Brown, Ali, Stone, & Jewell, ; Brown & Lee, ). We sought to bring insights from our past work on these topics to understanding how factors rooted in childhood might relate to the political knowledge, attitudes, and behavior of individuals from diverse social groups.…”
Section: Politics and Child Developmentmentioning
confidence: 99%